2008
DOI: 10.1111/j.1601-183x.2008.00405.x
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol trait and transcriptional genomic analysis of C57BL/6 substrains

Abstract: C57BL/6 inbred mice have been widely used as research models; however, widespread demand has led to the creation of several B6 substrains with markedly different phenotypes. In this study, we report that two substrains of C57BL/6 mice, C57BL/6J (B6J) and C57BL/6NCrl (B6C), separated over 50 years ago at two different breeding facilities differ significantly in alcohol consumption and alcohol preference. The genomes of these two substrains are estimated to differ by only 1–2% of all gene loci, providing a uniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
72
5

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(88 citation statements)
references
References 44 publications
11
72
5
Order By: Relevance
“…Multiple copy-number variants have also been discovered among B6 substrains (Egan, Sridhar, Wigler, & Hall, 2007;Mulligan et al, 2008), as well as between C57BL/6J strains obtained from different breeders (Watkins-Chow & Pavan, 2008). Additionally, expression profiling of several brain regions from C57BL/6J and C57BL/6NCrl indicate differential regulation of multiple transcripts between the two strains (Mulligan et al, 2008).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Multiple copy-number variants have also been discovered among B6 substrains (Egan, Sridhar, Wigler, & Hall, 2007;Mulligan et al, 2008), as well as between C57BL/6J strains obtained from different breeders (Watkins-Chow & Pavan, 2008). Additionally, expression profiling of several brain regions from C57BL/6J and C57BL/6NCrl indicate differential regulation of multiple transcripts between the two strains (Mulligan et al, 2008).…”
Section: Introductionmentioning
confidence: 96%
“…Additionally, expression profiling of several brain regions from C57BL/6J and C57BL/6NCrl indicate differential regulation of multiple transcripts between the two strains (Mulligan et al, 2008). C57BL/6J mice exhibit a higher recombination frequency than C57BL/6N mice when crossed with the BALB/c donor strain (Goto, Ebukuro, & Itoh, 2005), suggesting the possibility of different numbers and, possibly, types of recombinations when using these two substrains as the recipient strain for backcrossing mice containing the 129-derived donor transgene.…”
Section: Introductionmentioning
confidence: 98%
“…Although the two studies used the same a4 KO and WT progenitors (Ross et al, 2000) and they were back-crossed to C57BL6 mice for at least 10 generations, the C57BL6 substrain used for back-crossing in the Cahir et al (2011) study was not reported. This is an important distinction, as critical behavioral differences between the various C57BL6 substrains (in particular with C57BL6/J, the substrain used in our studies) have been reported (Mulligan et al, 2008;Mekada et al, 2009;Matsuo et al, 2010). Furthermore, the Cahir et al (2011) study used a different route of administration of nicotine (i.p.…”
Section: A6* Nachrs Subtypes In Nicotine Cppmentioning
confidence: 99%
“…However, all such studies (including this report) compared naive mice drinking alcohol and did not study postdependent drinking per se. Here we observe a positive relationship in which loss of Ap3m2 function results in increased withdrawal severity and increased preference in a strain of mouse (B6) with an already high alcohol preference (Mulligan et al 2008). It is important to note that the allelic effects on behavior in both QTL analyses were in the same direction with respect to B6/I, suggesting that the candidate at the Chr 8 locus should impact both behaviors in the same direction although other segregating loci may dissociate these effects.…”
Section: Discussionmentioning
confidence: 75%
“…The two-bottle free-choice methods were followed as previously described (Bachmanov et al 2002;Mulligan et al 2008). Individually housed mice (null n = 20, wild type n = 19) were presented with one tube containing an ethanol solution (The Jackson Lab Store/VWR International, Radnor, PA) made in sterilized, acidified (pH 2.5-3.0) water provided by the research animal facility.…”
Section: Two-bottle Choice Alcohol Preference Testmentioning
confidence: 99%